Modified lateral positioned flap with platelet-rich fibrin graft for treatment of denuded root surfaces: A clinical study - Abhishek Ashok Kurdukar; Priyanka Abhishek Kurdukar; Nitin Hemchandra Dani (Wolters Kluwer Medknow Publications, 2017)
Background: Root coverage (RC) procedures such as lateral positioned flap (LPF) have been used since long time but with limited success and specific indications. Aim: This prospective clinical study was designed to evaluate clinically the effect of modified LPF (mLPF) with platelet-rich fibrin (PRF) graft for the treatment of denuded root surfaces. Materials and Methods: Fifteen isolated Miller's Class I and II gingival recession of single-rooted teeth were selected for the study. Scaling and root planing was done, and oral hygiene instructions were given to the patients. Plaque index, gingival index, and recession parameters (probing depth, gingival recession height, clinical attachment level [CAL], and width of keratinized tissue [WKT]) were assessed at baseline. Following this, mLPF with PRF was done at the recession sites, and parameters were assessed at 3 and 6 months. Statistical Analysis: To analyze the posttreatment effect, paired t-test was performed at relevant degrees of freedom and 95% confidence level. Results: The mean percentage of RC attained was 72.2% at 3 months and 73.5% at 6 months. The WKT shows a mean gain of 2.93 mm at 3 months and 3 mm at 6 months. Conclusion: mLPF with PRF produced statistically significant reduction in recession depth and gain in both CAL and WKT by the end of 6 months.